Die korporatiewe identiteit van organisasies - Louise Nieuwmeijer (Communicare)
Millions are spent each year by organisations in every part of the world on planning, projecting and changing corporate identities. Very little is done however to understand the underlying phenomenon. It is essential therefore first to examine the nature and characteristics of corporate identity before analysing it. Problems in researching corporate identity and possible solutions will also be discussed in this paper.